FAKTOR YANG BERPENGARUH TERHADAP KEPATUHAN MASYARAKAT PADA PROTOKOL KESEHATAN DALAM MENCEGAH PENYEBARAN COVID-19 - Riyadi Riyadi; Putri Larasaty (Politeknik Statistika STIS, 2020)
The Covid-19 pandemic is one of the events threatening all around the world particularly in health sector. The widespread of this virus causes the most crucial issue to stop it immediately. Various kinds of policies have been made by the government to end the spread. However, on the other hand, the community is critically required to comply with health protocols as a serious effort to stop it. This study aims to analyze the level of community compliance in implementing health protocols in their daily lives, as well as to determine the socio-demographic factors that affect compliance with health protocols in society in Indonesia. The data used in this study is derived from the 2020 Social Demographic Impact of Covid-19 Survey from BPS. This analysis uses descriptive and regression analysis. The empirical results show that the average adherence index of male respondents is lower than that of female respondents, and there is a tendency that young people are more disobeying about health protocols with a relatively lower average adherence score compared to the older people. In addition, the socio-demographic characteristics that affect the level of community compliance with health protocols are respondent reaction status, perceptions of the effectiveness of independent isolation, level of concern about Covid-19 news, level of concern about traveling outside the home, gender, education level, marital status, health status, and age.